اﺗﺟﺎھﺎت طﻠﺑﺔ اﻟﻣرﺣﻠﺔ اﻟﺛﺎﻧوﯾﺔ واﻹﻋدادﯾﺔ ﻧﺣو اﻟﺗدرﯾس اﻟﻣدرﺳﻲ واﻟﺧﺻوﺻﻲ ﻋﻠﻰ وﻓق ﺑﻌض اﻟﻣﺗﻐﯾرات )ﺑﺣث ﻣﺳﺗل ﻣن رﺳﺎﻟﺔ ﻣﺎﺟﺳﺗﯾر( (Journal of the College of Education for Women, 2019)
There are many problems in education lead to a decline in its level,and the erosan of any development takes place ,if these problems serve as asnake or ascourge for the education , the private teaching is the head Because of their impact on the level of students.